STRATEGI DALAM MENINGKATKAN KEPATUHAN MASYARAKAT TERHADAP PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 - Sa’adah, Qheniyyatus; Nugroho, Setiyo Adi (Jurnal Keperawatan Profesional, 2022)
Corona virus disease (covid-19) is an infectious disease. Prevention of covid is by complying with health protocols. Knowledge is one of the factors of non-compliance, knowledge can be increased through education. The research method we use here is literature review using electronic databases through international and national journals such as google scientist, science direct, pro-quest, jstor with the keyword "Strategy In Increasing Public Compliance With Health Protocols During The Covid-19 Pandemic" The inclusion criteria used by the author is to limit the articles or journals published in the last five years starting from 2017 to 2021. This literature review uses 14 articles that meet the criteria. The conclusion in the results of the literature review study above is one method to improve community compliance is to use a combination strategy between offline and online learning using audio-visual and print and through social media can increase knowledge to carry out health protocols.